The Effect of Polycystic Ovarian Syndrome on the Physical Status of Women in Reproductive Age - ali, Azhar; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: To Assess the Effect of Physical Status of Polycystic Ovarian Syndrome on Women in Reproductive Age, To Find out the Relationship Between Polycystic Ovarian Syndrome and Women’s Physical Health (Acne , Hirsutism , Weight Gain , Irregular Menstrual Period),&To Identify the Association of Physical Status to polycystic ovarian syndrome and Some Socio Demographic Characteristic (Age ,Occupation & Obesity ), and Reproductive Characteristic(Gravida ,Para ,Abortion &Menstrual Regularity). Methodology :a descriptive analytical study was conduct on Non-probability (purposive sample) of (100)women who suffering from polycystic ovarian syndrome in reproductive age in infertility counseling from three hospitals at Baghdad city which include al- yarmouk teaching hospital ,Baghdad teaching hospital , and Kamal Al-Samaraee Hospital/ fertility and IVF at al-karck and al- Russafa sectors . Study implemented for the period of 2nd January 2013 to 30April 2013. A questionnaire was used as a tool of data collection to fulfill with objective of the study and consisted of two parts, including part I 1-socio-demographic characteristic 2- a reproductive information, 3-menstrual cycle information& 4-Previous medical history. And part II includes questions about hormonal and physical status of polycystic ovarian syndrome symptoms to women samples. A pilot study was carried out to test the reliability of the questionnaire and content, and validity was carried out through the 21 experts. Descriptive and inferential statistical analyses were used to analyze the data. Results: the results revealed that (83%) of the women in the study group were between the ages of (20-34) years 89%) were housewives, (77%) were primary school graduates and (66%) were suffering from low socio-economic status, (99%) were suffering from infertility, (88%) suffer from irregular menstrual cycle, (87%) The duration of the menstrual cycle has a (2-7) days, and (51%) suffer from severe pain during menstruation ,(30%) suffer from polycystic ovary syndrome in addition to the genetic percentage sisters infected during the study identified it (22%). Recommendations: The study recommended the development of programs and awareness sessions for disease polycystic ovarian syndrome for women living with for the purpose of learn how to deal with the disease, as well as how to prevent complications, the development of courses for nurses, especially present in the centers of infertility awareness and deliver new information about what’s new research and methods of treatment and how to deal with patient